Cosmoe's Wiener getaway - Brallier, Max (Aladdin, 2015)
Meet Cosmoe, the Earth-Boy. He's captain of the Neon Weiner, the finest flying food truck in the galaxy. Along with his bud, Big Humphree, he spends his days cruising the cosmos and staying crazy busy
Keywords: Food trucks / Juvenile fiction; Frankfurters / Juvenile fiction; Interplanetary voyages / Juvenile fiction; Frankfurters; Comic